The night before Christmas - Moore, Clement Clarke, 1779-1863.; Rackham, Arthur, 1867-1939. (New York : Weathervane Books : distributed by Crown Publishers, 1976)
The well-known poem about an important Christmas visitor.
Keywords: Santa Claus -- Juvenile poetry; Christmas -- Juvenile poetry; Children's poetry, American; Santa Claus -- Poetry; Christmas -- Poetry; American poetry; Narrative poetry